PENDIDIKAN KESEHATAN SENAM KAKI DIABETIK TERHADAP TINGKAT PENGETAHUAN KELUARGA DENGAN DIABETES MELLITUS DI DESA PIJIHARJO, MANYARAN, WONOGIRI - Nita Yunianti Ratnasari; Putri Utami (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
Diabetes Mellitus (DM) is a metabolic disease characterized by chronic hyperglycemia (high sugar) due to failure of insulin secretion, where normal sugar levels are between 80-120 mg / dL. Lack of patient and family knowledge can increase the risk of diabetes mellitus complications. To improve the prevention of complications, diabetic foot gymnastic health education is given. The aim of the study is to determine the effect of diabetic foot gymnastics health education on the level of knowledge of families with Diabetes Mellitus. This research type is qualitative with descriptive case study approach. The population in this study is all the people of Pijiharjo Village who experienced Diabetes Mellitus. The sample of 3 respondents families with Diabetic Mellitus. The Instruments use Standard Operating Procedures (SOP), leaflets, flipcharts, Counseling Event Unit (SAP), questionnaire sheet.Test analysis using review data. The action taken is diabetic foot gymnastics health education. This health education was done 1 days for 1 hour. All three respondents experienced an increase in knowledge as evidenced by the ability to answer the questionnaire before and after being given health education, from the category of insufficient (40% -67%) to a good category (80% -100%).From the case studies it was found that the level of respondents' knowledge increased as evidenced by the ability to answer the questionnaire before and after being given health education, from the category of insufficient (40% -67%) to a good category (80% -100%). This increase in the level of knowledge is influenced by the level of education, socioeconomic, age, and experience of obtaining prior health education.